2017
DOI: 10.1021/acs.organomet.7b00592
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon-Soluble Bis(trimethylsilylmethyl)calcium and Calcium–Iodine Exchange Reactions at sp2-Hybrized Carbon Atoms

Abstract: Hydrocarbon-soluble and highly reactive [(L) x Ca(CH 2 SiMe 3 ) 2 ] (L = tetrahydropyran, x = 4 (2a); L = tmeda, x = 2 (2b)) is synthesized by the metathesis reaction of Me 3 SiCH 2 CaI (1-I) with KCH 2 SiMe 3 . The durability of 2a in tetrahydropyran solution at 0 °C is sufficiently high for subsequent chemical transformations. The reaction of ICH 2 SiMe 3 with calcium in diethyl ether yields unique cage compound 3). We demonstrate that alkylcalcium complexes are valuable reagents for calcium−iodine exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The substitution of a halide in arylcalcium iodides by a metathetical approach with potassium pseudohalides (e.g., bis(trimethylsilyl)amide, diphenylphosphanide) was already investigated . Furthermore, the synthesis of bis(trimethylsilylmethyl)calcium followed a similar procedure through the reaction of trimethylsilylmethylcalcium halide with KCH 2 SiMe 3 . A similar approach was studied for trimethylsilylmethylcalcium iodide to elucidate the influence of an alkyl group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substitution of a halide in arylcalcium iodides by a metathetical approach with potassium pseudohalides (e.g., bis(trimethylsilyl)amide, diphenylphosphanide) was already investigated . Furthermore, the synthesis of bis(trimethylsilylmethyl)calcium followed a similar procedure through the reaction of trimethylsilylmethylcalcium halide with KCH 2 SiMe 3 . A similar approach was studied for trimethylsilylmethylcalcium iodide to elucidate the influence of an alkyl group.…”
Section: Resultsmentioning
confidence: 99%
“…[30] Furthermore, the synthesis of bis(trimethylsilylmethyl)calcium followed as imilar procedure through the reaction of trimethylsilylmethylcalcium halide with KCH 2 SiMe 3 . [27] As imilar approach was studied for trimethylsilylmethylcalcium iodide to elucidate the influence of an alkyl group. Thus, The molecular structure and atom labeling scheme of [Me 3 SiCH 2 Ca(pmdeta){N(SiMe 3 ) 2 }] (5b)a re depicted in Figure 4.…”
Section: Halide Exchange Reactionsmentioning
confidence: 99%
“…The successful isolation of well-defined calcium σ–alkyls has been historically dependent upon the use of sterically demanding and/or electronically stabilized (benzyl or α-triorganosilyl) organic anions. Lappert and co-workers, for example, reported the first dialkylcalcium, [(diox) 2 Ca­{CH­(SiMe 3 ) 2 } 2 ] ( 1 , diox = 1,4-dioxane) in 1991, while similar utilization of the same or closely related sterically demanding silylalkyl ligands has since enabled the synthesis of a wide variety of both homo- and heteroleptic organocalcium derivatives. In contrast, the indisputable authentication of the methyl calcium derivative, [CaMe 2 ] n ( 2 ), was only achieved by Anwander and co-workers in 2018 . In a similar vein, we have recently reported that the isolation of longer chain calcium ethyl, n- butyl and n -hexyl homologues, compounds 8 – 10 , may be achieved through reactions of the dimeric β-diketiminato calcium hydride, [(BDI)­CaH] 2 (BDI = HC­{(Me)­CN-2,6- i -Pr 2 C 6 H 3 } 2 ), compound 3 , with the terminal alkenes, ethane, 1-butene, and 1-hexene (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…In organocalcium chemistry "heavy Grignard reagents" [R'CaX]( R ' = aryl, alkenyl, neosilyl;X = Br,I )h ave been established, which can be prepared from activated calcium metal (Ca*) and organic halogen compounds RX in ethereal solvents via direct synthesis. [39] If the presence of halide is undesired, reagents such as dibenzyl species [(thf) x Ae(CH 2 Ar) 2 ]( Ae = Ca, [40] Sr, [41] Ba [41,42] ), silyl alkyls [(do) x Ae{CH(SiMe 3 ) 2 } 2 ]( Ae = Ca, [43,44] Sr, [43,44] Ba), [44] [Ca{C-(SiMe 3 ) 3 } 2 ], [45] [(thf) 2 Ca{C(SiHMe 2 ) 3 } 2 ], [46] [(do) x Ca(CH 2 SiMe 3 ) 2 ], [47] or calcium allyls [Ca(C 3 H 5 ) 2 ] n [48] and [(thf) 2 Ca{C 3 H 3 (SiMe 3 ) 2 } 2 ] [49] display versatile precursors. Only very recently the synthesis of the "simple" calcium alkyl [CaMe 2 ] n has been described.…”
Section: Potential Precursorsmentioning
confidence: 99%